Peran Media Sosial dalam Berdakwah untuk Generasi Milenial - Efendi, Erwan; Primadani, Rizky; Dinda; Ul Hanifah , Rita (VISA: Journal of Vision and Ideas, 2023)
This research aims to find out how the current millennial generation uses social media, technological developments have given rise to interesting phenomena in today's society, namely the emergence of instantaneous lifestyle and global culture. This article uses a specific type of library research, consisting of a number of tasks related to library data collection techniques. Data collection methods include collecting information from libraries or primary sources of da'wah literature through blogs, books, articles, scientific journals and social media. Content analysis is one way of analyzing data. Technological developments have produced results in Islamic da'wah. There are many places where it is, there are many people who are in the middle of the year, and there are many different types of people, there are many other places in the country, they are very old and there are many more. people. Technological developments cannot be denied, such as social media, sometimes we are not aware of the content that can change us so we fall into it. If you have a good idea of ​​the time you want, you have to live with the new generation, mileage, easy, which will be your content. There is no generative mileage that emerges from the background, but rather a man's business in the middle, so the content of generative mileage is different from previous generations.